SIPRAJA's impact on Community Engagement can be seen from the public service revolution: Dampak SIPRAJA terhadap Keterlibatan Masyarakat dapat dilihat dari revolusi pelayanan publik - Sentifolia, Shendya Rossi; Mursyidah, Lailul (Indonesian Journal of Public Policy Review, 2024)
This research evaluates the effectiveness of SIPRAJA in Porong Village, Indonesia, aiming to enhance public service quality. Despite challenges like low community participation, the study identifies factors hindering and supporting SIPRAJA and assesses its impact using qualitative methods. Results show strategic planning, policy coordination, and effective monitoring as key to its success, emphasizing the importance of improved socialization for community engagement. Highlights: SIPRAJA Program Evaluation: Assessing public service effectiveness in Porong Village. Key Success Factors: Strategic planning, policy coordination, and community engagement. Community Participation: Improving socialization for enhanced public service involvement. Keywords: SIPRAJA, public service effectiveness, community engagement, strategic planning, qualitative research